A Regression Analysis of Motivations for Saudi University Male Student Volunteers. Issue 45 (20th October 2019) - Alkadi, Rana; Jiang, Guoping; Aldamer, Shafi
Abstract: As a major national asset for promoting social development, volunteer groups have grown rapidly worldwide and have brought significant benefits to individuals, communities, and society in general. Volunteering is encouraged and common among Muslims in the Middle East, but there is rare study on why they volunteer. This study used multiple regression to explore what motivates Saudi male university students to volunteer with a sample of 223 subjects. The results show that all predictor variables such as pro-social personality, values function, career function, social function, enhancement function, protective function, and learning function of volunteering, community identity, institutional facilitation, and Islamic cultural motivation, are statistically significantly correlated to students' volunteering intentions, but these factors contribute to the ordinary least square regression model at different levels. Only career ( B = 0.217), social ( B = 0.212), learning ( B = 0.280), and enhancement functions ( B = 0.230) of volunteering have statistically significant influence on Saudi university male students' volunteering intention. Findings highlight a need for a focus on instrumental needs of volunteers by government and NGOs. In regards to future research, gender and educational impacts on volunteers' motive should be explored.